How to cheat at VoIP security - Porter, Thomas; Gough, Michael 1963- (Syngress, 2007)
Newly converged networks are vulnerable; this book details these attacks and the defense techniques and tools to use against them!
Includes bibliographical references and index
Keywords: COMPUTERS / System Administration / Email Administration; Computer networks / Security measures; Internet telephony -- Security measures; Computer networks -- Security measures